Hubungan Faktor Instrinsik dan Ekstrinsik terhadap Kejadian Diare pada Balita di Desa Noelbaki Kecamatan Kupang Tengah Kabupaten Kupang - Iren Melinda Maubana; Soni Doke; Eryc Z. Haba Bunga (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Diarrhea diseases are still a health problem worldwide. Diarrhea is the second leading cause of death in children under five. There are instrinsic and extrinsic factors that influence the occurrence of diarrhoea in children under five, such as exclusive breastfeeding for children under five, nutritional status of children under five, maternal habits of not washing hands, and lack of clean water availability. Data on cases of diarrhoea, in toddlers in Noelbaki Village, Central Kupang District, Kupang Regency in 2023 were 53 cases. The purpose of this study was to analyse the relationship between exclusive breastfeeding, nutritional status, maternal behaviour of washing hands with soap, and the availability of clean water to the incidence of diarrhoea in toddlers in Noelbaki Village, Kupang Tengah Sub-district, Kupang Regency. The type of research used was analytical survey research with a retrospective approach with a case control study design. This research was conducted in Noelbaki Village, Kupang Tengah Subdistrict, Kupang Regency. The population in this study were mothers of toddlers as many as 1,042, with a total sample of 74 respondents consisting of 34 case samples and 34 control samples, with simple random sampling technique. The statistical test used was chi square. The results showed that there was a relationship between exclusive breastfeeding (p=0.002), nutritional status of toddlers (p = 0.024), hand washing with soap behaviour (p=0.001), and availability of clean water (p=0.020) to the incidence of diarrhoea in toddlers.